Rescuing eGFP-Tagged Canine Distemper Virus for 40 Serial Passages Separately in Ribavirin- and Non-Treated Cells: Comparative Analysis of Viral Mutation Profiles - Liu, Fuxiao; Wang, Ning; Lin, Jiahui; Wang, Qianqian; Huang, Yilan; Zhang, Youming; Shan, Hu (Frontiers in Cellular and Infection Microbiology, 2021)
Due to lacking a proofreading mechanism in their RNA-dependent RNA polymerases (RdRp), RNA viruses generally possess high mutation frequencies, making them evolve rapidly to form viral quasispecies during serial passages in cells, especially treated with mutagens, like ribavirin. Canine distemper virus (CDV) belongs to the genus Morbillivirus. Its L protein functions as an RdRp during viral replication. In this study, a recombinant enhanced green fluorescence protein-tagged CDV (rCDV-eGFP) was rescued from its cDNA clone, followed by viral identification and characterization at passage-7 (P7). This recombinant was independently subjected to extra 40 serial passages (P8 to 47) in ribavirin- and non-treated cells. Two viral progenies, undergoing passages in ribavirin- and non-treated VDS cells, were named rCDV-eGFP-R and -N, respectively. Both progenies were simultaneously subjected to next-generation sequencing (NGS) at P47 for comparing their quasispecies diversities with each other. The rCDV-eGFP-R and -N showed 62 and 23 single-nucleotide mutations (SNMs) in individual antigenomes, respectively, suggesting that the ribavirin conferred a mutagenic effect on the rCDV-eGFP-R. The spectrum of 62 SNMs contained 26 missense and 36 silent mutations, and that of 23 SNMs was composed of 17 missense and 6 silent mutations. Neither the rCDV-eGFP-R nor -N exhibited nonsense mutation in individual antigenomes. We speculate that the rCDV-eGFP-R may contain at least one P47 sub-progeny characterized by high-fidelity replication in cells. If such a sub-progeny can be purified from the mutant swarm, its L protein would elucidate a molecular mechanism of CDV high-fidelity replication.